2017
DOI: 10.1177/1352458517706038
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and physical functioning in children with multiple sclerosis and acute disseminated encephalomyelitis

Abstract: Background and Objective:Fatigue and physical impairments are a major concern in children with multiple sclerosis (MS) and after acute disseminated encephalomyelitis (post-ADEM). We here aimed to evaluate the interaction between fatigue, exercise capacity, motor performance, neurological status, and quality of life (HRQoL).Methods:In this cross-sectional study, data of 38 children (MS n = 22, post-ADEM n = 16), aged 4–17 years attending our national pediatric MS center, were studied. Fatigue was measured with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Fatigue has not been evaluated before in patients with anti-NMDAR encephalitis. However, it is known to be a common disabling symptom in pediatric acquired brain injury, 22 , 23 making our results that fatigue was associated with poorer QoL plausible. This finding is supported further by the frequent reporting of fatigue by patients as the most disabling symptom often hampering normal participation.…”
Section: Discussionmentioning
confidence: 59%
“…Fatigue has not been evaluated before in patients with anti-NMDAR encephalitis. However, it is known to be a common disabling symptom in pediatric acquired brain injury, 22 , 23 making our results that fatigue was associated with poorer QoL plausible. This finding is supported further by the frequent reporting of fatigue by patients as the most disabling symptom often hampering normal participation.…”
Section: Discussionmentioning
confidence: 59%
“…Fatigue, mood disorders, anxiety and negative coping strategies could correlate with a negative school performance in these patients, and may interact with cognitive impairment as well [1416]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed reduced age-expected brain growth in monophasic ADS patients, especially ADEM, indicating irreversible and continuing changes occurring in the CNS even in the absence of chronicity [ 35 ]. Furthermore, recent studies have shown long-term residual deficits in ADEM and monophasic patients, such as a higher prevalence of motor problems, lower physical activity and fatigue [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canadian studies about childhood MS have highlighted young people's feelings of loss and grief and the challenges integrating treatment regimens and physical limitations into their daily lives (Boyd & MacMillan, ; Thannhauser, ; Thannhauser, Mah, & Metz, ). In addition, quantitative studies have discovered that young people with MS report lower health‐related quality of life (HRQoL) scores (Mowry et al, ) and have suggested that the fatigue they commonly experience may be associated with depression, reduced HRQoL, and lower school performance (Carroll, Chalder, Hemingway, Heyman, & Moss‐Morris, ; Toussaint‐Duyster, Wong, Van der Cammen‐van Zijp, Van Pelt‐Gravesteijn, & Catsman‐Berrevoets, ). To our knowledge, there have been no in‐depth qualitative studies conducted about young people's experiences of living with MS outside of Canada.…”
Section: Introductionmentioning
confidence: 99%